Precise HER2 Protein Degradation via Peptide‐Conjugated Photodynamic Therapy for Enhanced Breast Cancer Immunotherapy - Guo, Changyong; Gao, Fei; Wu, Guoyuan; Li, Jinqiu; Sheng, Chunquan; He, Shipeng; Hu, Honggang (Advanced science, 2025)
Breast cancer, the most prevalent malignancy among women, frequently exhibits high HER2 expression, making HER2 a critical therapeutic target. Traditional treatments combining the anti‐HER2 antibody trastuzumab with immunotherapy face limitations due to toxicity and tumor microenvironment immunosuppression. This study introduces an innovative strategy combining HER2‐targeting peptides with the photosensitizer (PSs) pyropheophorbide‐a (Pha) via a gelatinase‐cleavable linker, forming self‐assembling nanoparticles. These nanoparticles actively target breast cancer cells and generate reactive oxygen species (ROS) under near‐infrared light, effectively degrading HER2 proteins. Upon internalization, the linker is cleaved, releasing Pha‐PLG and enhancing intracellular photodynamic therapy (PDT). The Pha‐PLG molecules self‐assemble into nanofibers, prolonging circulation, boosting immune induction, and activating CD8+ T cells, thus promoting a robust anti‐tumor immune response. In vivo, studies confirm superior biosafety, tumor targeting, and HER2 degradation, with increased cytotoxic T cell activity and improved antitumor immunity. This integrated strategy offers a promising new avenue for breast cancer treatment. The self‐assembling nanomaterial PPC facilitates photo‐controlled degradation of the HER2 protein in conjunction with PDT, thereby reshaping the tumor microenvironment and augmenting the efficacy of tumor immunotherapy.